DENOSUMAB IN BONE-RELATED DISORDERS: CURRENT CLINICAL APPLICATIONS AND SAFETY CONSIDERATIONS — A NARRATIVE REVIEW - Smutkiewicz, Weronika; Teterycz, Weronika; Goździejewska, Wiktoria; Jaworek, Łukasz; Zimka, Gabriela; Bjorgen, Krystian; Jasińska , Lilianna; Roman, Magdalena; Lipiarz, Martyna; Niespodziewański, Michał (International Journal of Innovative Technologies in Social Science, 2026)
Denosumab is a fully human monoclonal antibody directed against the receptor activator of nuclear factor kappa-B ligand (RANKL), a central mediator of osteoclast differentiation, activation, and survival. Denosumab, acting by interfering with the RANKL pathway, provides powerful anti-resorptive activity and serves as an effective treatment modality for numerous conditions associated with bones. This narrative review summarizes the current evidence regarding the mechanism of action, pharmacokinetic and pharmacodynamic properties, clinical applications, and safety profile of denosumab. Denosumab has demonstrated substantial efficacy in osteoporosis, with significant increases in bone mineral density and reductions in vertebral, non-vertebral, and hip fracture risk. In oncology, it is widely used for the prevention of skeletal-related events in patients with bone metastases and multiple myeloma. It has also emerged as an effective targeted therapy in giant cell tumor of bone. Despite its broad clinical utility, denosumab therapy is associated with important safety considerations. These include hypocalcemia, osteonecrosis of the jaw, atypical femoral fractures, and the rebound phenomenon following treatment discontinuation. Rebound phenomenon is characterized by rapid bone turnover and increased risk of multiple vertebral fractures. These challenges highlight the importance of careful patient selection, monitoring, and long-term treatment planning. Denosumab represents a cornerstone therapy in the management of bone-related disorders due to its targeted mechanism and robust clinical efficacy. However, its reversible pharmacological profile necessitates individualized therapeutic strategies to optimize outcomes and minimize long-term risks.